With Death, an Orange Segment Between Our Teeth, poems by Marie-Claire Bancquart - Bancquart, Marie-Claire (Orison Books, 2023)
With Death, an Orange Segment Between Our TeethMarie-Claire BancquartTranslated from the French by Wendeline A. Hardenberg *Available for pre-order.* Orison Bookspaper / 178 pp. / $18.00bilingualISBN: 978-1-949039-42-9Distributed to the trade by Itasca Books952-223-8373 / orders@itascabooks.comPublication Date: November 7, 2023 ABOUT THE BOOK Marie-Claire Bancquart (1932–2019) was a prolific and prize-winning French poet, novelist, essayist, and critic. In her poetry, she combines an erudite vocabulary and references to classical literature with an earthy sensibility and a fascination with experiencing the smallest moments of everyday life fully. The deceptive simplicity of her poems lays bare the mysteries underlying the world we inhabit and our very existence. Wendeline A. Hardenberg’s careful and skillful translations are sure to broaden the audience for this significant poet as yet too little known outside of France. PRAISE Deeply philosophical, these poems, originally published in French when the author was in her seventies, focus on the meaning of existence. The poet reminds us that our lives—“seven liters of water wrapped in skin”—are “small,” but “the universe [is] in us / us in the universe.” From our “ephemeral perch on the earth,” writing achieves a kind of immortality, producing “a few words warmed by the journey, / that scatter outside, vouching / that you gave them a little extra life.” Readers will be grateful to Hardenberg for carefully shepherding these provocative poems into English. —Nancy Naomi Carlson, recipient of The Oxford-Weidenfeld Translation Prize Strange and wonderful translations of strange and wonderful poems... Marie-Claire Bancquart’s voice is utterly unique; her poems—by turns lyrical and jarring, mystical and forthright, tender and brutal—sing and clamor in your head long after you’ve read them. Like their French originals, Hardenberg’s excellent translations glitter and dart and unsettle; they dodge like wrestlers, then they grab you by the throat and won’t let go. This is rich writing to come back to again and again; each time you’re ambushed by some startling image or phrase or notion that you hadn’t noticed before. A vital book, both in the sense of its aliveness and its urgency.—Bill Johnston, recipient of The PEN Translation Prize ABOUT THE AUTHOR & TRANSLATOR Marie-Claire Bancquart (1932–2019) was a prolific and prize-winning French poet, novelist, essayist, and critic, as well as a Professor Emerita of French literature at the Sorbonne. Her final book, De l'improbable, précédé de Mo(r)t, was published by Éditions Arfuyen in 2020. Wendeline A. Hardenberg studied at Smith College and Indiana University, where she earned master’s degrees in Comparative Literature with a focus on translation and Library Science. She is the translator of numerous books, including The Bookshop of Forgotten Dreams by Emily Blaine, Will You Ever Change? by Aurélie Valognes, and Project Anastasis by Jacques Vandroux. Hardenberg’s translations have been published in Asymptote, Columbia Journal, Metamorphoses, Tupelo Quarterly, Two Lines, and other places. She lives in New Haven, Connecticut. SAMPLE POEM Close The blackberriesare clotted profusely in the bushes we are so close to the secret of this worldthat it seems to be awaitingjusta small steplike onto a balcony, to smell a flower. We don’t move that would be to wound the beingalmost managing to bein view of the fruits’ black boiling.
Keywords: dept.lib; literary-poetry

Exploring the Use of Common Strict Search Criteria in Nursing Literature Searches - Truex, Eleanor Shanklin; Spinner, Emily; Hillyer, Jean; Ettien, A'Llyn; Wade, Sarah; Calhoun, Courtney; Wolf, Grace; Hedreen, Rebecca; Heimlich, Layla; Nickum, Annie; Vonderheid, Susan C. (Nurse Educator, 2023)
Background: Health sciences librarians and nursing journal contributors have expressed concern about the impact of using strict parameters when searching the literature. Purpose: The purpose of this study was to explore the use of strict search criteria (eg, 5-year rule, “nurse as author”) by direct care nurses and nursing students. Methods: Fourteen online focus groups were conducted with 54 participants: direct care nurses, health sciences librarians, nursing faculty, and nursing students. Nursing faculty and health sciences librarians were included as participants to add perspective to the origins and effects of the use of stringent search criteria. Results: The majority of the nurses viewed the 5-year rule and nurse as author search limits favorably, while noting that a strict date range may hamper successful searching. Librarians viewed these search criteria more unfavorably but recognized the value of topic-appropriate search limits. Conclusion: Reliance on strict limits can be detrimental to pertinent results; however, appropriate use is essential for relevant results. Pedagogy focused on searching the nursing literature needs to emphasize that limits are tools to be used judiciously.
Keywords: dept.lib; peer-reviewed